Aggregated filter‐feeders govern the flux and stoichiometry of locally available energy and nutrients in rivers. (16th March 2021) - Hopper, Garrett W.; Chen, Shuo; Sánchez González, Irene; Bucholz, Jamie R.; Lu, YueHan; Atkinson, Carla L.
Abstract: Biogeochemical cycling has often been characterized by physical and microbial processes, yet animals can be essential mediators of energy and nutrients in ecosystems. Excretion by aggregated animals can be an important local source of inorganic nutrients in green food webs; however, whether animals are a source of dissolved energy that can support brown food webs is understudied. We tested whether animal aggregations are a substantial flux of bioavailable dissolved organic matter (DOM) by studying spatially stable, biogeochemical hotspots formed by filter‐feeding freshwater mussels. We used parallel‐factor analysis to quantify DOM fluorescent components composition of mussel excretion and expected digestive breakdown of particulate food sources would lead to excretion of labile DOM. Next, we combined measured excretion rates of DOM, ammonium ( NH 4 +, N) and phosphorous (SRP; P) for 22 species with biomass estimates for 14 aggregations to quantify contributions of DOM, N and P to local availability. Because mussels occupy distinct stoichiometric niches, we anticipated that differences in species biomass and assemblage structure would elicit different flux and stoichiometries of aggregate excretion. Aggregate dissolved organic carbon (DOC) excretion was minor (1%–11%) compared to N (12%–2, 860%) and P (1%–97%), yet generalities across assemblages emerged regarding organic matter transformation by mussels towards labile protein‐like compounds compared to abundant aromatic, humic compounds in ambient water. Aggregate excretion of labile DOM was a substantial pool of bioavailable energy, contributing 2%–114% of local labile DOM. Spatial differences in assemblage structure led to strong differences in aggregate flux and stoichiometry driven by biomass and stoichiometric trait expression of species with contrasting dominance patterns. Under the nutrient conditions of our study (high C:nutrient), biogeochemical hotspots associated with low‐trophic position animal biomass may indirectly control energy flow to the brown food web by shifting C:nutrient stoichiometry available to microbes or directly by increasing the flux of microbially available DOM. Collectively, our results highlight a potentially substantial flux of labile energy and nutrients to microbial communities through the transformation of ingested organic matter by aggregations of animals and emphasize that shared functional trait classification may not translate into shared ecological function. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Resumen: El ciclo biogeoquímico se ha caracterizado a menudo por procesos físicos y microbianos, pero los animales pueden ser mediadores esenciales de energía y nutrientes en los ecosistemas. La excreta de animales agregados puede ser una fuente local importante de nutrientes inorgánicos en las redes alimentarias basadas en producción primaria, sin embargo, no se ha estudiado si los animales son una fuente de energía disuelta que puede sostener las redes alimentarias basadas en detritívoros. Analizamos si las agregaciones de animales son un flujo sustancial de materia orgánica disuelta (MOD) biodisponible mediante el estudio de puntos calientes biogeoquímicos espacialmente estables formados por náyades filtradoras. Usamos análisis de factores paralelos para cuantificar la composición de los componentes fluorescentes de MOD en la excreta de las náyades y esperamos que la digestión de alimentos particulados conduciría a la excreción de MOD lábil. A continuación, combinamos las tasas medidas de excreción de MOD, amonio ( NH 4 +, N) y fósforo (SRP; P) para 22 especies, con estimaciones de biomasa de 14 agregaciones, para cuantificar las contribuciones de MOD, N y P a la disponibilidad local. Debido a que las náyades ocupan distintos nichos estequiométricos, anticipamos que las diferencias en la biomasa de las especies y la estructura de las colonias provocarían diferentes flujos y estequiometrías de excreción agregada. La excreción agregada de carbono orgánico disuelto (COD) fue menor (1%–11%) que la de N (12%–2, 860%) y P (1%–97%), sin embargo, surgieron generalidades en las colonias con respecto a la transformación, efectuada por las náyades, de materia orgánica a compuestos de proteínas lábiles en comparación con los más abundantes compuestos húmico‐aromáticos encontrados en el agua ambiental. La excreción agregada de MOD lábil fue una reserva sustancial de energía biodisponible, contribuyendo del 2 al 114% del MOD lábil local. Las diferencias espaciales en la estructura de las colonias generaron diferencias remarcables en el flujo agregado y la estequiometría, impulsadas por la biomasa y la expresión de rasgos estequiométricos de especies con patrones de dominancia contrastantes. En las condiciones de nutrientes de nuestro estudio (alto C: nutriente), los puntos calientes biogeoquímicos asociados con la biomasa de animales de posición trófica baja pueden controlar indirectamente el flujo de energía a la red trófica de suelo cambiando el ¨C: estequiometría de nutrientes¨ disponible para los microbios o directamente aumentando el flujo de MOD disponible microbianamente. En conjunto, nuestros resultados destacan un flujo potencialmente sustancial de energía lábil y nutrientes, a las comunidades microbianas a través de la transformación de materia orgánica ingerida por agregaciones de animales y enfatizan que la clasificación compartida de rasgos funcionales puede no traducirse a una función ecológica compartida.